Comparison of Face to Face vs. Group Training on Self-pulse Rate taking Ability of Patients - Habibollah Saadat; Roxana Sadeghi; Maryam Jannatipour; Alireza Abadi; Zahra Saadat; Saeed Alipour Parsa (Publisher: Shahid Beheshti University of Medical Sciences, 2019)
Introduction: Determining the rate and regularity of peripheral arterial pulses has a major role in assessing the clinical status of patients with cardiovascular disorders. We compared two training methods on the ability of patients to take their radial pulse rate accurately.Methods: Three-hundred patients were randomly divided into two arms. One arm received individual face-to-face training and the other arm received group training via displaying an animation movie. Immediately after the training and then after 48 hours, the patients were tested by a nurse to find out whether they have learned the correct technique of taking radial pulse rate or not.Results: Immediately after the intervention, 84.9% in face-to-face arm and 81.8% in group training arm were able to correctly count their radial pulse rate (P = 0.536). After 48 hours, 71.7% in face-to-face and 60.8% in group training arm were able to correctly count their radial pulse rate (P = 0.051).Conclusions: Both methods were effective to improve the ability of the patients to count their radial pulse rate correctly though face-to-face method was marginally superior to group training.